Hypothalamic-pituitary-adrenal axis, subjective, and thermal stress responses in midlife women with vasomotor symptoms. Issue 4 (April 2021) - Nathan, Margo D.; Wiley, Aleta; Mahon, Pamela B.; Camuso, Julie; Sullivan, Kathryn; McCormick, Kathleen; Srivastava, Akanksha; Albert, Kim; Newhouse, Paul; Joffe, Hadine
Abstract: Objective: Dysregulated responses to experimental stress paradigms may indicate exposure to chronic stress. Vasomotor symptoms (VMS) are linked with diminished quality of life and psychological stress, but induced stress responsivity has received limited investigation. We examined whether women with and without VMS differ in their evoked hypothalamic-pituitary-adrenal axis, subjective, hemodynamic, and thermal stress responses. Methods: A total of 37 midlife women (27 VMS+; 10 VMS–) completed 2 experimental stress paradigms: (1) Montreal Imaging Stress Task (MIST; computerized social-evaluative stressor) and (2) Quantitative Sensory Testing (QST; thermal stress task). Responses on a five-domain (range 0-50) Visual Analog Scale, salivary cortisol (hypothalamic-pituitary-adrenal axis), and hemodynamic indices (blood pressure, heart rate) were measured before and after each task to compare within-person change between groups. Thermal sensitivity was assessed on the QST. Results: On the MIST, the VMS+ group showed a smaller cortisol release (0.01 vs 0.07 μg/dL; P = 0.046; corresponding to 54% vs 83% increases), and subjective stress response (21.2- vs 31.1-point Visual Analog Scale increase, P = 0.05; corresponding to 2427% vs 2863% increases) but no hemodynamic difference, compared to the VMS– group. The QST did not provoke stress responses via cortisol release or subjective report, but the VMS+ group tended to perceive heat at a higher temperature (38.5°C vs 36.4°C, P = 0.08). Conclusions: Women with VMS exhibited both diminished cortisol and subjective stress responses to the MIST, and reduced thermal sensitivity on QST compared to women without VMS. Dysregulated stress responsivity provides preliminary evidence suggesting that VMS may represent a chronic stress condition.